Utilizing data mining to discover knowledge in construction enterprise performance records - Lee, Jen-Rong; Hsueh, Sung-Lin; Tseng, Hung-Ping (Journal of Civil Engineering and Management, 2008)
Although Data Mining (DM) has been applied extensively in information systems and identified as a crucial tool for automatic data analysis and enterprise knowledge inference, still the practicability of DM has been little explored in the construction industry in particular. This study is conducted using data from actual practice in the customer service department of the target enterprise. Starting with data preparation, decision tree analysis and domain knowledge inference, practical verification is performed and previously unknown knowledge is discovered. Two practical barriers to enterprise information mining are found: the separation of information among various information systems and lack of key information attributes. Hence, there is a significant limitation on practical information data mining to generate new information, and only with a proper information integration one can benefit from the potential practical application of DM. Utilizuotas duomenų kaupimas Santrauka. Nors duomenų ryšys buvo plačiai taikomas informacinėse sistemose ir apibrėžiamas kaip pagrindinė priemonė duomenims automatiškai analizuoti ir įmonės žinioms pateikti, tačiau praktinis jo taikymas statybos pramonėje buvo mažai nagrinėtas. Šis tyrimas atliktas naudojantis praktine informacija, surinkta Tikslinių įmonės vartotojų paslaugų departamente. Pradedant duomenų rengimu, sprendimo medžio analize ir įmonės žinių pateikimu, yra atliekamas praktinis tikrinimas ir identifikuojamos prieš tai nenustatytos žinios. Atrasti du praktiniai duomenų ryšio kliuviniai: skirtingų informacijos sistemų informacijos atskyrimas ir pagrindinių informacijos atributų trūkumas. Tai yra didelis praktinės informacijos duomenų ryšio apribojimas, trukdantis naujai informacijai kurti. Tik tinkamai integruojant informaciją, galima pasiekti naudos iš praktinio duomenų ryšio taikymo. Reikšminiai žodžiai: data mining, informacinės sistemos, statybos pramonė, įmonės žinios, paslaugos ir priežiūra. First Published Online: 14 Oct 2010